2021
DOI: 10.3389/fonc.2021.716876
|View full text |Cite
|
Sign up to set email alerts
|

DIAPH1 Promotes Laryngeal Squamous Cell Carcinoma Progression Through Cell Cycle Regulation

Abstract: The diaphanous related formin 1 (DIAPH1) protein is involved in the regulation of dynamic cytoskeleton reorganization, which is closely related to mitosis and the cell cycle. Cell cycle disorders are generally regarded as important underlying causes of many cancers. In the current study, we have revealed that DIAPH1 expression is an independent prognostic factor for overall survival in patients with laryngeal squamous cell carcinoma (LSCC) and that DIAPH1 promotes colony formation, cell proliferation, and G1/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…DIAPH1 is an essential regulator of tissue shape change and of cells in epithelial tissues that initiate invasion ( Fessenden et al, 2018 ). Clinical studies have shown that the expression of the DIAPH1 protein is significantly upregulated in tissues of patients with colorectal cancer and laryngeal cancer ( Lin et al, 2014 ; Yang et al, 2021 ). High DIAPH1 protein levels are associated with poor prognosis in ovarian cancer patients ( Schiewek et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…DIAPH1 is an essential regulator of tissue shape change and of cells in epithelial tissues that initiate invasion ( Fessenden et al, 2018 ). Clinical studies have shown that the expression of the DIAPH1 protein is significantly upregulated in tissues of patients with colorectal cancer and laryngeal cancer ( Lin et al, 2014 ; Yang et al, 2021 ). High DIAPH1 protein levels are associated with poor prognosis in ovarian cancer patients ( Schiewek et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%